2011
DOI: 10.1177/0333102410392606
|View full text |Cite
|
Sign up to set email alerts
|

Joint hypermobility syndrome: A common clinical disorder associated with migraine in women

Abstract: Preliminary studies suggested that headache disorders are more common in patients with joint hypermobility syndrome (JHS). The objectives of this study were to determine if the prevalence, frequency, and disability of migraine differ between female patients with JHS and a control population. Twenty-eight patients with JHS and 232 controls participated in the case-cohort study. Participants underwent a structured verbal interview and were assigned a diagnosis of migraine based on criteria of the International C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 35 publications
2
36
0
4
Order By: Relevance
“…It is a frequent complaint among those having hEDS as well [Jacome, ; Maeland et al, ; Murray et al, ; Hamonet et al, ]. More specifically, migraines were seen at a greater frequency and disability compared to a control population [Hakim and Grahame, ; Bendik et al, ; Puledda et al, ].…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…It is a frequent complaint among those having hEDS as well [Jacome, ; Maeland et al, ; Murray et al, ; Hamonet et al, ]. More specifically, migraines were seen at a greater frequency and disability compared to a control population [Hakim and Grahame, ; Bendik et al, ; Puledda et al, ].…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Bendik et al [] reported multiple headache types among 28 hEDS female patients in an interview‐style case‐control study. Headaches, in particular migraine, was higher in prevalence and more often more disabling than the control population (N = 232).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Migraine, common in the general population, is more prevalent in women [Nappi and Nappi, ]. Migraine is also more prevalent among EDS which also has a female predilection [Bendik et al, ; Castori and Voermans, ; Castori et al, ]. Therefore, EDS may be considered a risk factor for migraine.…”
Section: Headache In Ehlers–danlos Syndromementioning
confidence: 99%